Expanding the Scope of Crosslink Identifications by Incorporating Collisional Activated Dissociation and Ultraviolet Photodissociation Methods - Cammarata, Michael B. (Anal Chem, 2018)
With the advent of new crosslinking chemistries, analytical technologies, and search algorithms, crosslinking has become an increasingly popular strategy for evaluating tertiary and quaternary structures of proteins. Collisional activated dissociation remains the primary MS/MS method for identifications of peptide crosslinks in high throughput workflows. 193 nm ultraviolet photodissociation (UVPD) has emerged as an alternative ion activation method well-suited for characterization of peptides and has been found in some cases to identify different peptides or provide distinctive sequence information than obtained by collisional activation methods. Complementary high energy collision dissociation (HCD) and UVPD were used in the present study to characterize protein crosslinking for bovine serum albumin, hemoglobin, and E. coli ribosome. Crosslinks identified by HCD and UVPD using bis(sulfosuccinimidyl)suberate (BS3), a homobifunctional amine-to-amine crosslinker, and 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMTMM), a heterofunctional amine-to-carboxylic acid crosslinker, were evaluated in the present study. While more unique BS3 crosslinks were identified by HCD, UVPD and HCD provided a complementary panel of DMTMM crosslinks which extended the degree of structural insight obtained for the proteins.